A ESTIMAÇÃO DE COMPONENTES DE VARIÂNCIA NOS EXPERIMENTOS EM LÃTICE QUADRADO - Pimentel-Gomes, F. (REVISTA DE AGRICULTURA, 2020)
A ESTIMAÇÃO DE COMPONENTES DE VARIÂNCIA NOS EXPERIMENTOS EM LÃTICE QUADRADO